2023
DOI: 10.2478/rjim-2023-0013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reliability and Validity of the RALE and BRIXIA Chest-X Ray Scores in Patients Hospitalized with COVID-19 Pneumonia

Themistoklis Paraskevas,
Platon M. Dimopoulos,
Anastasios Kantanis
et al.

Abstract: Introduction: Chest X-rays are commonly used to assess the severity in patients that present in the emergency department with suspected COVID-19 pneumonia, but in clinical practice quantitative scales are rarely employed. Aims: To evaluate the reliability and validity of two semi-quantitative radiological scales in patients hospitalized for COVID-19 pneumonia (BRIXIA score and RALE score). Methods: Patients hospitalized between October 2021 and March 2022 with confirmed COVID-19 pneumonia diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The prognostic accuracy of the two scores for in-hospital mortality for all raters demonstrated good to excellent prognostic value having a consistent upward trend with significant differences between severity groups in both radiological scores. 12 At the same time, the number of chest CT requests in this pandemic has been reduced due to hassle in the subsequent necessity for intense infection control measures in CT suites as well as difficulties in mobilizing hypoxic patients, and the involvement of high radiation. 24 , 25 Depending on the extent of involvement by consolidation or GGOs in CXR, we considered a maximum score of 8 in our setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic accuracy of the two scores for in-hospital mortality for all raters demonstrated good to excellent prognostic value having a consistent upward trend with significant differences between severity groups in both radiological scores. 12 At the same time, the number of chest CT requests in this pandemic has been reduced due to hassle in the subsequent necessity for intense infection control measures in CT suites as well as difficulties in mobilizing hypoxic patients, and the involvement of high radiation. 24 , 25 Depending on the extent of involvement by consolidation or GGOs in CXR, we considered a maximum score of 8 in our setting.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 8 Till now, several severity scoring systems in CXR have been used for quantitative and objective estimation of lung involvement and progression 10 and some evaluated the area of lung involved, while others focused on infiltrative patterns. 10 , 11 Paraskevas et al 12 suggested two scores, BRIXIA and radiographic assessment of lung edema score (RALES), which are reliable and can be used to assess the prognosis of patients with COVID-19 requiring hospitalisation.…”
Section: Introductionmentioning
confidence: 99%